An Investigative Review for Pharmaceutical Analysis of 1, 4-Dihydropyridine-3, 5-Dicarboxylic Acid Derivative: Cilnidipine. (7th May 2021) - Chaudhari, Suraj R.; Shirkhedkar, Atul A.
Abstract: Hypertension is commonly a quiet condition, and it expands the risk of heart diseases and stroke. Calcium delivers a substantial role in cardiovascular functions and hence is essential for cardiac automaticity and functioning. Calcium channel antagonists are the choice of drugs for the management of cardiovascular diseases; they precisely stop the introduction of calcium through L-type calcium channels are existing channels in the heart. Cilnidipine belongs to the class 4th generation calcium channel blockers as a foremost therapeutic agent used in the treatment of hypertension and heart diseases. This review article focuses on an inclusive account of crucial analytical methodologies used for the pharmaceutical analysis of cilnidipine in pure forms, biological samples and pharmaceuticals. According to literature reports several analytical techniques such as hyphenated techniques, high-performance thin-layer chromatography, high-performance liquid-chromatography, capillary electrophoresis, voltammetry, UV/Vis-spectrophotometry, and Fourier-transform infrared spectroscopy approaches have been used for determination of cilnidipine alone or in the combined dosage form. We have also discussed the pharmacopeial assay methods, physicochemical properties, and also depict the stacked column chart for year wise publication count for cilnidipine. From literature, concluded that the high-performance liquid-chromatography and UV/Vis-spectrophotometry methods are the most prevailing methods for the analysis of cilnidipine. The data presented in this review may provide a very significant base for further studies on cilnidipine in the area of drug analysis.